The Holocaust the Third Reich and the Jews - Engel, David 1951- (Routledge, Taylor & Francis Group, 2021)
"This book offers a survey of the encounter between the Third Reich and European Jewry. Pointing out the difficulties historians face in interpreting the ever-expanding documentary record, it includes treatment of the role of non-Germans in the Holocaust, consideration of the much-debated nexus between the Holocaust and modernity and discussion on how 'the Holocaust' developed as a distinct historical topic. Including a useful selection of original documents, many never before anthologised in English, a chronology, glossary and Who's Who, David Engel's book will be welcomed by anyone trying to get to grips with this complex and far-reaching subject"
Keywords: Geschichte 1939-1945; Geschichte 1933-1945; Judenvernichtung; Judenverfolgung; Deutschland; Europa; Holocaust, Jewish (1939-1945); World War, 1939-1945 / Atrocities; National socialism; Germany / Politics and government / 1933-1945; Jews / Germany / History / 1933-1945; Atrocities; Jews; Politics and government; Germany; 1933-1945; History